BREEDING AND EXPLOITATION OF NATIVE SALMONIDS SPECIES WITH A VIEW TO DIVERSITY THE FISH PRODUCTION AND PRESERVE THE BIODIVERSITY - ANCA BOARU; R.M. VODĂ; I.V. PETRESCU MAG.; I. FALKA; CRISTINA HEGEDUŞ; I. DOMBI (Scientific Papers Animal Science and Biotechnologies, 2023)
In Romania, the salmon breeding is the second branch of pisciculture as importance, but the obtained production is very small (about 1240 to; ANPA, 2005) and enough limited as bred species (brown trout - Salmo trutta fario, brook trout - Salvelinus fontinalis and rainbow trout - Oncorhynchus mykiss). The brown trout (Salmo trutta fario L.) and the huchen (Hucho hucho L.) represent two species with big economical, biological and culinary value, and to capitalize and promote the Romanian aquatic and endemic potential we consider timely and necessary that these ones to breed in specialized farms, with a view to diversity the fish production and to preserve the biodiversity. In the project, our consortium proposes projection and building of a pilot station for brown trout (Salmo trutta fario L.) and huchen (Hucho hucho L.) breeding in space and environment controlled, hall type, with control possibility of medium parameters. By application of modern and performed fish breeding system it can be promoted new methods, techniques and technologies, which have as final aim the obtaining of some diversity fish productions, and evidently superior given to those obtained in present days in trout farms from Romania.